KAJIAN FITOKIMIA DAN SIFAT ANTI BAKTERI JAMUR ENDOFITIK RS-1 PADA RANTING ANDROGRAPHIS PANICULATA (SAMBILOTO) DENGAN MEDIA PERTUMBUHAN BERAS MERAH - Melisa Yolanda; Sri Benti Etika; Riga Riga (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Andrographis paniculata (Sambiloto) was reported to produce secondary metabolites with various biological activities including antibacterial. The antibacterial compounds from sambiloto can also be explored from other sources. One of them is their endophytic fungi. The purpose of this research was to determine the antibacterial activity of endophytic fungi cultivated in red rice media. The steps of this research were isolation, cultivation, extraction, antibacterial test and test the content of secondary metabolites from endophytic fungi derived from the twigs of A. paniculata. An endophytic fungus labelled with RS-1 has been isolated from the twigs of A. paniculata. The results of the antibacterial activity test showed that the ethyl acetate extract of the fungus RS-1 had the ability to inhibit the growth of all tested bacteria at concentrations of 1%, 3%, and 5%. The ethyl acetate extract of the endophytic fungus RS-1 isolated from the A. paniculata has potential to produce antibacterial compound.